2010
DOI: 10.1097/bcr.0b013e3181c7ed30
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Opioid Administration on Resuscitation Volumes in Thermally Injured Patients

Abstract: Administration of resuscitation volumes far beyond the estimates established by burn-body weight resuscitation formulas has been well documented. The reasons behind this increase are not clear. We sought to determine if our resuscitation volumes had increased and, if so, what factors were related to their increase. A retrospective chart review identified 154 patients admitted with burns greater than 20% of their BSA during the years of 1975-1976 (period 1), 1990-1991 (period 2), and 2006-2007 (period 3). Chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
(58 reference statements)
0
8
0
1
Order By: Relevance
“…Since tracheal intubation is associated with increased fluids, this is another issue that might be addressed. Sullivan [63] and Wibbenmeyer [64] also suggested that large doses of opioids might be involved. The extreme rise in opioid administration in 1998–2002 likely followed the events described by Peck [65].…”
Section: Resultsmentioning
confidence: 99%
“…Since tracheal intubation is associated with increased fluids, this is another issue that might be addressed. Sullivan [63] and Wibbenmeyer [64] also suggested that large doses of opioids might be involved. The extreme rise in opioid administration in 1998–2002 likely followed the events described by Peck [65].…”
Section: Resultsmentioning
confidence: 99%
“…Sullivan and coauthors noted an increase in the use of opioid analgesics between the late 1970s and the early 2000s, which they termed opioid creep . The effect of more opioid use during burn shock is to increase the likelihood of hemodynamic instability and thus fluid needs . Possibly, changes in the medical fitness of the population, with an increased incidence of diabetes and substance addiction, may also affect fluid needs …”
Section: The Conundrum: Underresuscitation and Shock Versus “Fluid Crmentioning
confidence: 99%
“…28 The effect of more opioid use during burn shock is to increase the likelihood of hemodynamic instability and thus fluid needs. 29 Possibly, changes in the medical fitness of the population, with an increased incidence of diabetes and substance addiction, may also affect fluid needs. 30 In a thorough evaluation of the literature, Guilabert et al 77 performed a nonsystematic review to help determine the current evidence and recommendations for the early resuscitation of burn patients.…”
Section: The Conundrum: Underresuscitation and Shock Versus "Fluid Crmentioning
confidence: 99%
“…6 In another study of intensive insulin therapy in pediatric burn-injured patients, the investigators found that intensive insulin therapy reduced resting energy expenditure in the first week after burn injury, improved mitochondrial oxidation capacity, and improved hepatic glucose metabolism. 7 Taken together, these two articles build an argument that in burn patients, intensive insulin therapy may reduce inflammation and improve energy utilization.…”
Section: Critical Carementioning
confidence: 95%